GAP PEMIKIRAN KEBERADAAN PAJAK BERDASARKAN PERSPEKTIF SYARIAT ISLAM - Syukur, Dudung Abdul (MONETER, 2013)
Indonesia's state-Muslim majority (88%) is the largest number of moslem society in the world. As a citizen of Indonesia, moslem also has a tax liability for those who are qualified. Payment of tax liability is a manifestation of the role of the state and taxpayers to directly and jointly carry out tax obligations for the financing of state and national development. Appropriate philosophy of tax laws, paying taxes is not only an obligation, but it is the right of every citizen to participation state financing and development national. There are several opinions about zakat obligation. This different opinion should be seated in the proper proportions in order to enable the mutual understanding that brings benefit to the future of the Muslim nation Indonesia in particular and generally